Manajemen Pembaharuan Kepala Sekolah dalam Meningkatkan Kompetensi Guru - Neni Ningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The study aims at evaluating the school principal renewals management to improve teachers competence at SMP Negeri 1 Arga Makmur Bengkulu Utara regency. The study was an evaluative descriptive study. The subjects were the school principal, teachers and staffs. The techniques to collect the data were questionnaire, observation, and documentation. The data analysis was conducted through four components including data collection, data reduction, data presentation and conclusion drawing/verification. The finding showed that the school principal renewals management was in 'good' category with score ranges between 51- 62 out of the total score 75. In conclusion, the school principal renewals management was successful to improve teachers competence, particularly the competence of pedagogy, personality, social, and professional. Keywords: Management, Renewals, School Principal